Measuring Service Quality Gaps in Village Administration: A SERVQUAL-Based Approach to Community Satisfaction Assessmen - Aqilla Sintiya; Muhammad Yasin Simargolang; M. Faisal Afiff Tarigan (Ali Institute of Reseach and Publication, 2026)
This study examines the quality of administrative services in Sei Mencirim Village by applying the Service Quality (SERVQUAL) method. A quantitative descriptive approach was adopted, with data collected through questionnaires distributed to residents who actively use village administrative services. The research instrument was developed based on the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that all service dimensions show positive gap values between community perceptions and expectations, with an overall average gap of 0.85. This result suggests that the services provided by the village administration generally meet, and in several aspects exceed, community expectations. Among the five dimensions, assurance recorded the highest gap value, reflecting strong public confidence in staff competence and service security. In contrast, reliability showed the lowest gap value, although it remained within the satisfactory category. Overall, the study reveals that community members are satisfied with the administrative services provided by Sei Mencirim Village. Nevertheless, improving service reliability—particularly in terms of consistency, accuracy, and timeliness—remains necessary to ensure sustainable service quality. This research contributes empirical evidence on village-level public service performance and offers practical insights for policymakers seeking to improve administrative service delivery through a SERVQUAL-based evaluation framework.